2015
DOI: 10.1007/s11136-015-0996-5
|View full text |Cite
|
Sign up to set email alerts
|

Short-term quality of life in patients undergoing colonic surgery using enhanced recovery after surgery program versus conventional perioperative management

Abstract: Short-term QOL in patients undergoing colonic cancer using ERAS program was better than that using conventional management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
15
0
2
Order By: Relevance
“…Wang et al used PROMs to evaluate patient outcomes and short-term quality of life in patients undergoing colonic surgery. 50 Fifty-seven patients were randomized to an ERP and 60 were randomized to conventional care. Using the EORTC QLQ-C30 and EORTC QLQ CR 29 (European organization for research and treatment of cancerquality of life for colorectal cancer questionnaire), they demonstrated that short term quality of life was better in patient in the ERP group on postoperative days 3, 6, 10, 14 and 21.…”
Section: Evaluation Of An Enhanced Recovery Pathwaymentioning
confidence: 99%
“…Wang et al used PROMs to evaluate patient outcomes and short-term quality of life in patients undergoing colonic surgery. 50 Fifty-seven patients were randomized to an ERP and 60 were randomized to conventional care. Using the EORTC QLQ-C30 and EORTC QLQ CR 29 (European organization for research and treatment of cancerquality of life for colorectal cancer questionnaire), they demonstrated that short term quality of life was better in patient in the ERP group on postoperative days 3, 6, 10, 14 and 21.…”
Section: Evaluation Of An Enhanced Recovery Pathwaymentioning
confidence: 99%
“…However, there has been limited research on patients' experiences of accelerated discharge after shortening of post-operative hospital stay [12]. Some studies have included measures of patient satisfaction with enhanced recovery programmes [13,14] and changes in QOL [15]. One study of ERP The final publication is available at Springer via http://dx.doi.org/10.1007/s00520-016-3158-6 4 after liver resection found that the substantial majority of patients rated their satisfaction with perioperative care as "good" or "excellent" both 3 days and 3 months post-discharge [14].…”
Section: Introductionmentioning
confidence: 99%
“…In a study that compared ERAS and conventional management in patients undergoing open colon surgery, ERAS patients had faster rehabilitation, decreased hospital LOS, and better shortterm quality of life (physical, emotional, cognitive, and social functioning). 6 In gynecological patients undergoing an ERAS-type pathway, patients reported higher levels of satisfaction with their care. 7,8 The financial models for ERAS protocols also may be favourable because of the reduced hospital LOS and improved surgical outcomes.…”
Section: Adult Evidencementioning
confidence: 99%